Influence of Life Style Factors on Barrett’s Oesophagus - A. Horna Strand; T. Franzén (Gastroenterology Research and Practice)
Background. Since the incidence of adenocarcinoma of the oesophagus is rising, the prognosis is poor, and surveillance programs are expensive and mostly cost ineffective, there is a need to increase the knowledge of risk factors in Barrett’s oesophagus and oesophageal cancer in order to be able to give attention to medical prevention and/or surveillance programs. Aim. To study if there is a correlation between the development of Barrett’s oesophagus and GOR (gastro oesophageal reflux), family history of GOR, and life style factors, such as alcohol, smoking habits, and mental stress. Methods. Fifty-five consecutively selected patients with Barrett’s oesophagus (BO) examined at Linköping University Hospital’s Oesophageal Laboratory were matched by sex, age, and duration of reflux symptoms with 55 GOR patients without Barrett’s oesophagus at the Oesophageal Laboratory. The medical charts in respective groups were examined for comparison of life style factors, mental stress, medication, duration of gastroesophageal acid reflux at 24 hr-pH-metry, and incidence of antireflux surgery and of adenocarcinoma of the oesophagus (ACO). Also, potential gender differences and diagnosis of ACO were studied. Results. Mean percentage reflux time on 24 hr-pH-metry was higher for the Barrett’s oesophagus group, 18% for women and 17% for men compared to 4% for women and 4% for men in the control group (P<0.05). Family history of GOR was more frequent in Barrett’s oesophagus patients (62%) than in the control group (35%) (P<0.05). Male patients with Barrett’s oesophagus had medical therapy for their GOR symptoms to a higher extent (38%) than male controls (65%) (P<0.05). No difference was found in the number of tobacco users or former tobacco users between Barrett’s oesophagus patients and controls. Barrett’s oesophagus patients had the same level of alcohol consumption and the same average BMI as the control subjects. Female patients with Barrett’s oesophagus rated themselves as more mentally stressed (67%) than the female controls (38%) (P<0.05). In the five-year medical chart follow-up, five of 55 patients developed adenocarcinoma among the Barrett’s oesophagus patients, none in the control group. Conclusions. Long reflux time and family clustering of GOR seem to influence the development of Barrett’s oesophagus. Smoking habits, alcohol consumption and BMI do not seem to have any impact on the development of Barrett’s oesophagus.